Influence of diabetes on short-term outcome after major hepatectomy: an underestimated risk? - Fischer, Christian; Fuchs, Juri; Stravodimos, Christos; Hinz, Ulf; Billeter, Adrian; Büchler, Markus W.; Mehrabi, Arianeb; Hoffmann, Katrin (BMC surgery, 2020)
Patient-related risk factors such as diabetes mellitus and obesity are increasing in western countries. At the same time the indications for liver resection in both benign and malignant diseases have been significantly extended in recent years. Major liver resection is performed more frequently in a patient population of old age, comorbidity and high rates of neoadjuvant chemotherapy. The aim of this study was to evaluate whether diabetes mellitus, obesity and overweight are risk factors for the short-term post-operative outcome after major liver resection.
Gesehen am 08.01.2021